Rapid pairing and resegregation of distant homologous loci enables double-strand break repair in bacteria - Badrinarayanan, Anjana (J Cell Biol, 2015)
Double-strand breaks (DSBs) can lead to the loss of genetic information and cell death. Although DSB repair via homologous recombination has been well characterized, the spatial organization of this process inside cells remains poorly understood, and the mechanisms used for chromosome resegregation after repair are unclear. In this paper, we introduced site-specific DSBs in Caulobacter crescentus and then used time-lapse microscopy to visualize the ensuing chromosome dynamics. Damaged loci rapidly mobilized after a DSB, pairing with their homologous partner to enable repair, before being resegregated to their original cellular locations, independent of DNA replication. Origin-proximal regions were resegregated by the ParABS system with the ParA structure needed for resegregation assembling dynamically in response to the DSB-induced movement of an origin-associated ParB away from one cell pole. Origin-distal regions were resegregated in a ParABS-independent manner and instead likely rely on a physical, spring-like force to segregate repaired loci. Collectively, our results provide a mechanistic basis for the resegregation of chromosomes after a DSB.